Semences et agrobiodiversité : pour une lecture ontologique des bio-communs locaux - Fabien Girard (Développement Durable et Territoires)
Farmers’ seed networks – the local bio-commons – have been, if not dismantled, at least made invisible in their inner dimension and downgraded to a resource status following a series of paradigmatic shifts. Past or current solutions, which rest on the categories of global public good or on the commons, fail to ensure the conservation and sustainable use of PGRFA. Notably, they have been unable to go beyond the conception of seed as a resource and to account for the various ontological status conferred upon it at the local level.While advocating a broader approach, the text calls for a re-conceptualization of the plant commons framework. Relying on a local-level approach, the new conceptual framework should emphasize the link between communities and resources, the ontological value of seed, and better underline the role of traditional institutions in the circulation of seed.